Sergiy Volodimirovich Goshovsky (On the sixty-year-old Jubilee) (Геологічний журнал, 2010)
On 31 May 2010, Sergiy V. Goshovsky, director of the Ukrainian State Geological Prospecting Institute, Doctor of Technical Sciences, Professor, Corresponding Member of Engineering Academy, Academician of the Ukrainian Oil and Gas Academy, Honored Industrial Worker of Ukraine, Honorable Mineral Resources Explorer and state employee of the first rank, celebrated his 60th anniversary.